1990
DOI: 10.1007/bf00150445
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection in primary unexplained infertility

Abstract: In recent years Chlamydia trachomatis has emerged as a significant cause of acute salpingitis and reproductory failure. In this study, 85 women suffering from primary infertility and 85 parous women as control group were screened for C. trachomatis genital infection by means of cell culture and antigen detection on genital samples as well as the detection of anti-chlamydial antibodies in blood. C. trachomatis was detected in 31.8% of infertile women and 5.8% of fertile subjects. Isolation of C. trachomatis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…21,[24][25][26][27][28] The higher prevalence rates were reported in Palestine (20.2%), Nigeria (28.0%), Netherlands (29.5%), Italy (31.8%), Iran (32.0%), and Tanzania (36.21%). [29][30][31][32][33][34] Studies from New Delhi, India observed also a higher prevalence of CT among infertile women than in current research (28.1% vs 15.6%). 35 The prevalence rate of CT among subfertile women in Vietnam in our study was within the reported range.…”
Section: Discussioncontrasting
confidence: 61%
“…21,[24][25][26][27][28] The higher prevalence rates were reported in Palestine (20.2%), Nigeria (28.0%), Netherlands (29.5%), Italy (31.8%), Iran (32.0%), and Tanzania (36.21%). [29][30][31][32][33][34] Studies from New Delhi, India observed also a higher prevalence of CT among infertile women than in current research (28.1% vs 15.6%). 35 The prevalence rate of CT among subfertile women in Vietnam in our study was within the reported range.…”
Section: Discussioncontrasting
confidence: 61%
“…Of the remaining 375 papers, 117 did not classify a definition of unexplained infertility. As a result, a total of 258 primary research papers with full text available were included …”
Section: Resultsmentioning
confidence: 99%
“…The requirement for intracellular growth on cultured mammalian cells makes detection of C. trachomatis by culture technically difficult and time consuming. Direct detection of C. trachomatis in endocervical samples with an antichlamydial monoclonal antibody or a chlamydial DNA probe is more rapid than culture but has a lower sensitivity (6,7) and still requires laboratory equipment. Development of DNA amplification assays has further increased the sensitivity of endocervical C. trachomatis detection (1,2).…”
mentioning
confidence: 99%